Exploration of the role of Hibiscus esculentus (okra) mucilage for the removal of phenothiazinium dyes from water body: Spectroscopic, thermodynamic and molecular modeling study - Md Kalimuddin Mandal; Mukti Mohammad; Nasima Yasmin; Harun Al Rasid Gazi; Md. Maidul Islam (Ecotoxicology and Environmental Safety, 2024)
Environmental pollution poses a major problem now a day. Several dyes, in the form of industrial waste, pollute water body and may cause adverse effects to human health. In this paper ADME and toxicity of fives Phenothiazinium group of dyes Methylene blue (MB), Azure A (AA), Azure B (AB), Azure C (AC) and Toluidine Blue O (TBO) were predicted using Swiss ADME and Protox II tools. Results showed these dyes may herm for living organism due to their carcinogenic, mutagenic and hepatotoxic properties. Removal efficiency of these dyes using okra plant product were determined using spectroscopic, thermodynamic and molecular modeling study. It was revealed that these dyes adsorb on the surface of okra leaf mostly at pH 7.0 and the adsorption isotherms were found to fit in Langmuir and Freundlich isotherm model, while Temkin model fails to do this. Mucilage present in different parts of okra plant plays a significant role on removal of these dyes and is able to remove near about 71–92 % of dyes from water body by itself. As this process did not fit in any of above said adsorption isotherm model, it may be suggested that some other mechanism may happen. Further studies explore that these dyes bound to the hydrophobic pocket of mucilage with binding affinity in the order of 105 M−1 and the bindings were exothermic in nature with enthalpy change in the range of − 2.94 to − 4.28 kcal/mole. Molecular docking study validate all the experimental results obtained from spectroscopic and thermodynamic study and enlighten the role of structure of dyes on their binding affinity to mucilage. This paper will help to systematically understand the role of okra plant products on removal efficiency of Phenothiazinium group of dyes with their structural variations.